IAENG Transactions on Engineering Technologies Special Issue of the International MultiConference of Engineers and Computer Scientists 2012 - Yang, Gi-Chul.; Ao, Sio-Iong.; Huang, Xu.; Castillo, Oscar. (Lecture Notes in Electrical Engineering,, 2013)
This volume contains revised and extended research articles written by prominent researchers participating in the conference. Topics covered include engineering physics, communications systems, control theory, automation, engineering mathematics, scientific computing, industrial engineering, and industrial applications. IAENG Transactions on Engineering Technologies: Special Issue of the International MultiConference of Engineers and Computer Scientists 2012 offers the state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.